PENERAPAN STRATEGI PEMASARAN SEBAGAI UPAYA MENINGKATKAN USAHA KECIL DAN MENENGAH WARGA DI KELURAHAN PANINGGILAN UTARA CILEDUG - Solihin, Dede; Susanto, Noto; Setiawan, Rahmad; Ahyani, Ahyani; Darmadi, Darmadi (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of this community service is to help businesses in promoting UMKM products in the Kelurahan Paninggilan Utara Ciledug. The method of community service activities begins with the preparation and field survey stages. The survey phase began with a direct discussion with the head of RT 001/013 Paninggilan Utara Urban Ciledug City to identify the needs, opportunities and challenges faced by UMKM entrepreneurs. Then, the socialization and training stage is carried out by the team. At this stage there are five things carried out by the service team, namely (1) explaining how to make attractive products, (2) finding a strategic location for businesses (3) making promotional content that is easily remembered by customers (4). And how to distribute the product so that it can reach the customer. (5). Online marketing. The results of the community service activities are as follows: Participants' knowledge in this case the residents of Kelurahan Paninggilan Utara Ciledug regarding marketing strategies prior to the majority PKM activities were in the category of not understanding. After the PKM activities are carried out and the presentation of the material is delivered, it is known that the participant's knowledge of the marketing strategy after it is delivered is increasingly increasing.